2015
DOI: 10.1007/s00726-015-2073-3
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic effect of p-chloro-diphenyl diselenide on glucose metabolism and mitochondrial function alterations induced by monosodium glutamate administration to rats

Abstract: The metabolic syndrome is a group of metabolic alterations considered a worldwide public health problem. Organic selenium compounds have been reported to have many different pharmacological actions, such as anti-hypercholesterolemic and anti-hyperglycemic. The aim of this study was to evaluate the effect of p-chloro-diphenyl diselenide (p-ClPhSe)2, an organic selenium compound, in a model of obesity induced by monosodium glutamate (MSG) administration in rats. The rats were treated during the first ten postnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In fact, hyperglycemia is a characteristic symptom of rats treated with MSG [Shen et al, ; Miranda et al, ]. In animal models, subcutaneous neonatal MSG administration induces neuroendocrine obesity through hypothalamic lesion: resulting in fat tissue accumulation, glucose intolerance, hyperinsulinemia, and insulin resistance [Shen et al, ; Miranda et al, ; Quines et al, ]. Furthermore, it has been demonstrated that hyperglycemia is associated with systemic insulin resistance and mitochondrial dysfunction in animal models of obesity induced by MSG administration [Shen et al, ; Miranda et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, hyperglycemia is a characteristic symptom of rats treated with MSG [Shen et al, ; Miranda et al, ]. In animal models, subcutaneous neonatal MSG administration induces neuroendocrine obesity through hypothalamic lesion: resulting in fat tissue accumulation, glucose intolerance, hyperinsulinemia, and insulin resistance [Shen et al, ; Miranda et al, ; Quines et al, ]. Furthermore, it has been demonstrated that hyperglycemia is associated with systemic insulin resistance and mitochondrial dysfunction in animal models of obesity induced by MSG administration [Shen et al, ; Miranda et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…route for 7 days. The dose of 10 mg/kg of ( p ‐ClPhSe) 2 was chosen based on our previous study group [Quines et al, ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…panel B). Accordingly, our previous data demonstrated the effectiveness of another organoselenium compound in normalizing the activities of hepatic enzymes in a model of metabolic disorder induced by glutamate monosodium in rats [Quines et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the induction of glutamate neurotoxicity involves the development of intracellular changes and subsequent events resulting in neuronal disintegration (Choi, 1994). Furthermore, it has been demonstrated that the MSG model, which consists of MSG administration to newborn rats, induces functional and behavioural alterations in adulthood, including obesity, hyperexcitability, pain sensitivity, anxiogenic-like and depressive-like behaviours, as well as impairment of memory (Quines et al 2014;Rosa et al 2015;Quines et al 2016).…”
Section: Introductionmentioning
confidence: 99%